Scientific discussion of selected viruses including COVID-19 in hot springs - Quiñones-Bolaños, Edgar; Rodriguez Cheu, Luis Eduardo; Sanchez Londoño, Yuly Andrea; Mehrvar, Mehrab; McCarthy, Lynda (Bogotá, 2020)
The objective of this study is to discuss selected viruses including COVID-19 and their potential elimination processes in hot springs. Studies in Colombia are limited and this scientific discussion provides necessary information regarding these viruses. This includes studies both in Colombia and international levels on the following subjects: i) the presence of viruses in hot springs, ii) the non- oxidative water treatment in hot springs, iii) the elimination strategies of viruses; and iv) the influence of COVID-19 in hot springs. The results of this discussion indicate that in order for thermal waters to guarantee the elimination of the viruses originating from faecal and nonfaecal derived, and the COVID-19 virus, a monitoring scheme is required to identify an effective disinfection of waters to control these pathogens.

El objetivo de este estudio es analizar virus seleccionados, incluido el COVID-19, y sus posibles procesos de eliminación en aguas termales. Los estudios en Colombia son limitados y esta discusión científica proporciona información necesaria con respecto a estos virus. Esto incluye estudios tanto en Colombia como a nivel internacional sobre los siguientes temas: i) la presencia de virus en aguas termales, ii) el tratamiento no oxidativo del agua en aguas termales, iii) las estrategias de eliminación de virus; y iv) la influencia del COVID-19 en aguas termales. Los resultados de esta discusión indican que, para que las aguas termales garanticen la eliminación de los virus de origen fecal y no fecal, y del virus COVID-19, es necesario un esquema de vigilancia que permita identificar una desinfección eficaz de las aguas para controlar estos patógenos.
Keywords: COVID-19 (Enfermedad); COVID-19 (Disease); Aguas termales; Hot springs; Virosis; Virus diseases; hot springs; viruses; faecally-derived; non-faecally derived; COVID-19